Orthopaedic Resident Remediation: Frequency, Interventions, and Outcomes. Issue 4 (18th December 2018) - Melton, William; Jackson, J. Benjamin; Koon, David; Grabowski, Gregory
Abstract : Background: Despite multiple studies in other areas of surgical resident education, there is no current literature regarding orthopaedic resident remediation. The goal of the present study was to use a survey format to determine the frequency of remediation, the underlying etiology, the intervention strategies utilized, and the outcomes. Methods: The program directors of all current 159 Accreditation Council for Graduate Medical Education-recognized orthopaedic residency programs in the United States were e-mailed a non-identifying digital survey. Follow-up e-mails were sent monthly for a 3-month period. The data remained anonymous, with no identifying information. The data are reported with use of descriptive statistics. Results: Seventy (44%) of 159 program directors responded; most were from academic institutions with 4 to 5 residents per class. One hundred and fifty-eight residents were remediated, with the greatest number being remediated during the third postgraduate year (PGY-3). Professionalism, patient care, and communication were the most common deficiencies requiring remediation. Mentorship, feedback, and probation were the most common interventions. Of the 117 residents for which the outcome was reported, 58 graduated on time, 14 graduated from another program, 25 graduated from another specialty, 14 were terminated, 3 pursued litigation, and 3 chose a non-medical career. Rehabilitation, didactics, feedback, and mentorship were associated with the highest rates of on-time graduation. Conclusions: Most remediated residents were PGY-3, suggesting increased scrutiny as residents moved from junior to senior responsibilities. The greatest number of deficiencies requiring remediation pertained to the affective domain, which highlights the importance of screening measures such as away rotations and interviews. The relationships formed during increased feedback sessions and mentorships can help problem residents to graduate on time.